2009
DOI: 10.1038/nrneph.2009.211
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic nephropathy: a disorder of oxygen metabolism?

Abstract: Chronic hypoxia induces sequential abnormalities in oxygen metabolism (for example, oxidative stress, nitrosative stress, advanced glycation, carbonyl stress, endoplasmic reticulum stress) in the kidneys of individuals with diabetes. Identification of these abnormalities improves our understanding of therapeutic benefits that can be achieved with antihypertensive agents, the control of hyperglycemia and/or hyperinsulinemia and the dietary correction of obesity. Key to the body's defense against hypoxia is hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 148 publications
(142 reference statements)
0
49
0
Order By: Relevance
“…5). The fact that NOX4 siRNA treatment partially blocked the generation of ROS would also suggest that ROS are derived from dual sources in MIOX-overexpressing cells under high glucose ambience, as has been described in various investigations related to diabetic nephropathy in various animal models (1,3,9,10,50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5). The fact that NOX4 siRNA treatment partially blocked the generation of ROS would also suggest that ROS are derived from dual sources in MIOX-overexpressing cells under high glucose ambience, as has been described in various investigations related to diabetic nephropathy in various animal models (1,3,9,10,50).…”
Section: Discussionmentioning
confidence: 99%
“…E, MIOX activity; at basal levels (LG), it was designated as 100%, and a relative percentage increase in various samples was calculated. A dosedependent increase in enzyme activity was observed with various concentrations of D-glucose but not with L-glucose or transfection of EV (E, columns [1][2][3][4][5]. However, MIOX-pcDNA transfection led to a ϳ2-fold increase in enzyme activity even at LG concentration, whereas it increased by another 50% under HG ambience, and it was normalized to almost basal levels with MIOX siRNA treatment (E, columns 6, 7, and 9).…”
Section: Effect Of Glucose On H 2 O 2 Generation and Relative Depletimentioning
confidence: 99%
“…Abnormalities in oxygen metabolism have been implicated in the development and progression of diabetic nephropathy and include hypoxia, oxidative stress, nitrosative stress, and advanced glycation and/or carbonyl stress (44,71,93). A role of hypoxia in chronic renal disease was proposed by Fine et al (39) and has been confirmed in human and animal models, including the diabetic kidney (96,134).…”
Section: Hypoxia Oxidative Stress and Tubulointerstial Fibrosis In mentioning
confidence: 81%
“…There has been considerable discussion about how renal hypoxia may contribute to progression of renal disease (18,39). However, it is well recognized that obesity can predispose to salt-sensitive hypertension well before there is evidence of kidney disease.…”
Section: Discussionmentioning
confidence: 99%